The Important Role of Social and Cultural Capital in Online History Learning during the Covid-19 Pandemic - Asriana Zainal Abidin (Newinera Publisher, 2020)
The study discussed the role of social and cultural capital in online history learning. Social capital and cultural capital have a close relationship with character education in the learning process and become one of the important factors in the success of an educational goal. Social and cultural capital has a very important role for this, with the application and development of social and cultural capital in history learning, the development of students, especially in terms of character education, will improve Online learning during the current Covid-19 pandemic. This social and cultural capital has several character values that can be developed for students in every lesson, especially history learning even though it is online. The character values contained in social capital include: beliefs, social networks, and norms.